Australia's 'New Security' Challenges - Hubbard, Christopher (2004)
This paper is in two parts. The first part undertakes a survey and critique of the theoretical foundations of the new security agenda, using the work of Professor Buzan and his collaborators Ole Waever and Jaap de Wilde as a sounding board in addressing several important and fundamental concerns about the nature of the new agenda. While in general agreement with these scholars on the need to renovate the security agenda, the paper discusses problems of conceptualization and analysis which their project discloses.The second part of the paper has two purposes. First, it discusses the broad sweep of regional and functional security challenges as seen from the Australian perspective. Secondly, it undertakes a small case study of the nature and significance of Australia's policy and actions in respect of the 1997 Kyoto Protocol to the 1992 Rio Framework Convention on Climate Change. In doing so, it seeks to point up the significance of this policy challenge to Australia in the context of the new security agenda.